1999
DOI: 10.1002/hep.510300213
|View full text |Cite
|
Sign up to set email alerts
|

Primary biliary cirrhosis once rare, now common in the United Kingdom?

Abstract: There is a widespread impression that the number of patients with the autoimmune liver disease primary biliary cirrhosis (PBC) is increasing, although its incidence and prevalence vary widely. Using thorough case-finding methods and rigorous definitions to assess changes in incidence and prevalence with time and to explore the symptomatology and mortality of the disease in a large group of unselected patients, we performed a descriptive epidemiological study of PBC in a well defined population over a fixed per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
141
2
6

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 215 publications
(163 citation statements)
references
References 22 publications
13
141
2
6
Order By: Relevance
“…12 Northeast England has one of the highest frequencies of PBC in the world, with an incidence of 32.2 new cases per million and a prevalence of 251 cases per million (940 cases per million women over age 40) in 1994.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Northeast England has one of the highest frequencies of PBC in the world, with an incidence of 32.2 new cases per million and a prevalence of 251 cases per million (940 cases per million women over age 40) in 1994.…”
Section: Discussionmentioning
confidence: 99%
“…The methods used to identify the Northeast England cohort of patients with PBC have previously been well described. 12 This cohort included all incident and prevalent cases of definite or probable PBC alive between January 1987 and December 1994 within a geographically defined area of Northeast England. The area of study comprised 6 adjacent health areas of Northeast England including Northumberland, Sunderland, North Durham, South Durham, South of Tyneside, and North of Tyneside.…”
Section: Methodsmentioning
confidence: 99%
“…Further, PBC constitutes a significant economic burden resulting in yearly costs of 69-115 million US dollars for hospital charges alone, as estimated by the Healthcare Cost and Utilization Project (HCUP). Both prevalence 3 and mortality 4 rates for PBC have been increasing over the past decade.…”
mentioning
confidence: 99%
“…1 There is considerable variation in its prevalence worldwide, being most common in Northern Europe and least common in the Indian subcontinent and Africa. 2 Like other diseases of autoimmunity there may be one or more genetic determinants to susceptibility in PBC.…”
mentioning
confidence: 99%
“…No population-based case-control studies have been conducted so far. However, the development of a local PBC case register based on a geographically defined population 1,15 provided the opportunity to conduct a population-based case-control study of PBC that investigated associations with new and previously suggested extrinsic factors. Given the large number of factors considered, this study was exploratory in nature.…”
mentioning
confidence: 99%